2022
DOI: 10.1172/jci153589
|View full text |Cite
|
Sign up to set email alerts
|

METTL23 mutation alters histone H3R17 methylation in normal-tension glaucoma

Abstract: Normal-tension glaucoma (NTG) is a heterogeneous disease characterized by retinal ganglion cell (RGC) death leading to cupping of the optic nerve head and visual field loss at normal intraocular pressure (IOP). The pathogenesis of NTG remains unclear.Here, we describe a single nucleotide mutation in exon 2 of the methyltransferase like 23 (METTL23) gene identified in a three-generation Japanese NTG family. This mutation caused METTL23 mRNA aberrant splicing, which abolished normal protein production and altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 63 publications
0
29
0
1
Order By: Relevance
“…This study by Pan et al highlights the role of histone arginine methylation in neurodegenerative processes and raises important questions for the field ( 8 ). Are there other targets of METTL23 that play critical roles in RGC survival?…”
Section: Epigenetics and Neurodegenerationmentioning
confidence: 94%
See 3 more Smart Citations
“…This study by Pan et al highlights the role of histone arginine methylation in neurodegenerative processes and raises important questions for the field ( 8 ). Are there other targets of METTL23 that play critical roles in RGC survival?…”
Section: Epigenetics and Neurodegenerationmentioning
confidence: 94%
“…The elegant study by Pan et al in this issue of the JCI describes a genetic cause of NTG and reports a mutant histone methyltransferase leading to NTG ( 8 ). The investigators identified a family of three generations of Japanese patients with NTG and a splicing mutation in the methyltransferase-like 23 ( METTL23 ) gene, which encodes a histone arginine methyltransferase.…”
Section: Epigenetics and Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Their conclusion aligns with that of a 2012 study by Zhang et al (2012) who report the RGC neuroprotective effects of broad-spectrum HDAC inhibitors following optic nerve crush. Pan et al (2022) mapped a mutation in the gene encoding Methyltransferase-like 23 ( METTL23 ) in a familial case of normal tension glaucoma. That research group demonstrated the possible significance of this mutation by demonstrating that mice overexpressing or lacking in Mettl23 develop glaucoma-like phenotypes in the absence of elevated IOP.…”
Section: Posttranslational Modifications In Glaucoma and Models Of Re...mentioning
confidence: 99%